Predictors of response and remission in patients with treatment-resistant depression: A post hoc pooled analysis of two acute trials of esketamine nasal spray. (May 2023) - Turkoz, Ibrahim; Nelson, J. Craig; Wilkinson, Samuel T.; Borentain, Stephane; Macaluso, Matthew; Trivedi, Madhukar H.; Williamson, David; Sheehan, John J.; Salvadore, Giacomo; Singh, Jaskaran; Daly, Ella
Highlights: Predictors of response to ESK+AD and AD+PBO were identified in patients with TRD. ESK+AD treatment, younger age, employment, and low anxiety predicted response. Fewer failed ADs in the current episode and early response also predicted response. Odds of achieving response were 68% higher with ESK+AD versus AD+PBO ( P  = 0.003). Our findings may identify patients mostly likely to benefit from ESK+AD treatment. Abstract: This exploratory post hoc analysis of two pooled 4-week, phase 3, double-blind, placebo- and active-controlled studies that compared esketamine nasal spray plus a newly initiated oral antidepressant (ESK+AD; n   =  310) with a newly initiated oral AD plus placebo nasal spray (AD+PBO; n   =  208) in patients with treatment-resistant depression (TRD) examined baseline patient demographic and psychiatric characteristics as potential predictors of response (≥50% reduction from baseline in Montgomery–Åsberg Depression Rating Scale [MADRS] total score) and remission (MADRS total score ≤12) at day 28. Overall, younger age, any employment, fewer failed ADs in the current depressive episode, and reduction in Clinical Global Impression-Severity (CGI-S) score at day 8 were significant positive predictors of response and remission at day 28. Treatment assignment was an important predictor of both response and remission. Patients treated with ESK+AD had 68% and 55% increased odds of achieving response and remission, respectively, versus those treated with AD+PBO. In the ESK+AD group, attainment of response and remission was more likely in patients who were employed, without significant anxiety at baseline, and who experienced a reduction in CGI-S score at day 8. Identification of predictors of response and remission may facilitate identification of those patients with TRD most likely to benefit from ESK+AD. Trial Registration: ClinicalTrials.gov: NCT02417064 (clinicaltrials.gov/ct2/show/NCT02417064) and NCT02418585 (clinicaltrials.gov/ct2/show/NCT02418585)